Lengthening Dry Spells Intensify Summer Heatwaves. Issue 19 (7th October 2022) - He, Bin; Zhong, Ziqian; Chen, Deliang; Liu, Junguo; Chen, Yaning; Miao, Chiyuan; Ding, Ruiqiang; Yuan, Wenping; Guo, Lanlan; Huang, Ling; Hao, Xingming; Chen, Aifang
Abstract: A lengthening of dry spells (DSLs) has been reported by some regional studies, but its linkage with heatwaves via the feedback between soil moisture and air temperature is still not clear on the global and continental scales. Here we examine increases in the length of DSLs during summer over the global continents using in situ precipitation records. Globally, the average DSL has increased by 0.46 day/decade since the 1970s along with increased high‐pressure anomalies which are found to be an important reason for the intensification of heatwaves as suggested by the robust and widespread relationships between the DSL and heatwave duration and severity in the northern extratropics. The average DSL associated with a heatwave declined over lands, implying a strengthening coupling between precipitation anomalies and heatwaves. The findings of this study suggest that the precipitation variations associated with changes in DSLs should be considered in attributions of temperature extremes. Plain Language Summary: Despite the little change of global mean precipitation over continents during the past decades, it can exert a great impact on land surface energy exchange through changes in precipitation timing, frequency, and the interval between precipitation events. Our study suggests a general lengthening of dry spells (DSLs) in summer over continents, which is likely attributed to the strengthening of high‐pressure anomalies. We also reveal a close and strengthening linkage between DSL length and summer heatwaves during the past decades. These findings are crucial for understanding the land‐atmosphere feedback in the context of climate change. Key Points: The average dry spell (DSL) length has increased by 0.46 day/decade over the global continents since the 1970s The robust and widespread relationships between the average DSL length and heatwave duration and severity were found The shortening average DSL length associated with heatwaves indicated an enhancing coupling process between DSL and heatwaves